Entrepreneurial Strategies in Ai-Enhanced Sports Marketing Platforms - Akbari, Mohsen; Naderi Nasab, Mehdi; Biniaz, Seyyed Abbas (Management Strategies and Engineering Sciences, 2024)
Artificial intelligence (AI) is transforming sports marketing by enabling more personalized fan experiences, enhancing customer engagement, and optimizing marketing operations. AI technologies such as machine learning, predictive analytics, and chatbots are widely used to drive innovation and create new revenue models in the sports industry. However, despite the benefits, the integration of AI in sports marketing comes with challenges related to technical implementation, economic risks, and ethical concerns. This article aims to review entrepreneurial strategies in AI-enhanced sports marketing platforms and explore their effectiveness in driving innovation, market expansion, and customer engagement. This narrative review uses a descriptive analysis method to synthesize literature from academic journals, industry reports, and case studies related to AI-driven marketing strategies in sports. The analysis focused on identifying key entrepreneurial approaches such as innovation, market penetration, partnerships, and revenue models within AI-enhanced sports marketing platforms. The study identified several successful entrepreneurial strategies enabled by AI, including innovation in product development through personalized fan engagement platforms and virtual reality experiences. AI also supports market expansion by enhancing digital advertising and enabling dynamic pricing. Strategic partnerships with technology companies are crucial for accessing advanced AI tools, while customer-centric strategies driven by AI have improved fan engagement. The analysis also highlighted the challenges associated with AI adoption, including high costs, data privacy issues, and ethical considerations. Nonetheless, AI-driven revenue models such as subscriptions and targeted advertising are creating new business opportunities. AI is reshaping sports marketing by enabling new entrepreneurial strategies that drive innovation, market growth, and customer engagement. While challenges exist, the future of AI in sports marketing holds significant potential for further growth and transformation